Current status and future prospects for oral care education in Bachelor of Nursing curriculums: A Japanese cross‐sectional study. Issue 2 (30th November 2022) - Haresaku, Satoru; Miyoshi, Maki; Kubota, Keiko; Obuse, Mika; Aoki, Hisae; Nakashima, Fuyuko; Muramatsu, Masumi; Maeda, Hitomi; Uchida, Souhei; Miyazono, Mami; Iino, Hidechika; Naito, Toru
Abstract: Objective: This study sought to investigate the current status and faculty members' perceptions of oral care education in Bachelor of Nursing curriculums in Japan. Method: Data were gathered through a questionnaire survey of 196 participants, who were faculty members in charge of oral care education in the basic, adult, gerontological, and home nursing fields, from 295 nursing schools that offered Bachelor degrees in nursing across Japan. Results: The quantitative data showed that 38.5% of the participants worked for less than 5 years as oral care educators, only 15.5% taught oral care in perioperative wards, only 62.2% used an oral care training simulator, and less than 30% believed that training in the prevention of oral diseases should be enhanced. From the descriptive responses, this study identified such problems as the inability of students to perform student‐on‐student and patient‐based oral care training owing to the risk of SARS‐CoV‐2 transmission, and the lack of teaching materials, time, and human resources, and cooperation with other nursing fields and health professionals. Conclusions: This study revealed several problems in oral care education in the Bachelor of Nursing curriculums in Japan. To tackle these challenges, this study suggests the development of an interdisciplinary course that unifies oral care education in nursing fields, in order to promote collaborative oral care education and to improve nursing students' knowledge and skills of oral care.